2014
DOI: 10.1007/s00128-014-1363-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cadmium and Copper Biosorption on Chlorella vulgaris

Abstract: Changes in protein levels and lipid compositions in algal cells indicate the severity of stress related to toxic concentrations of heavy metals. In this study, the effects of exposure to cadmium and copper on Chlorella vulgaris and its capacity to remove metals were evaluated. The data revealed ion removal activity by microalgae under all treatments and different levels of protein expression after 48 h of exposure. Furthermore, we analyzed lipids contents to characterize them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The literature and preliminary studies conducted by the authors showed that this is the proper time to reach equilibrium [3,5,19]. After that time the pH values were measured and afterwards the biomass was removed by filtration through a 0.45 µm membrane filter.…”
Section: Batch Experimentsmentioning
confidence: 99%
See 4 more Smart Citations
“…The literature and preliminary studies conducted by the authors showed that this is the proper time to reach equilibrium [3,5,19]. After that time the pH values were measured and afterwards the biomass was removed by filtration through a 0.45 µm membrane filter.…”
Section: Batch Experimentsmentioning
confidence: 99%
“…This situation is a result of industrial activities which are related to the population growth, urbanization and industrialization [1,2]. The toxic effect of heavy metals on the environment and living organisms is observed even at low concentrations, due to their accumulation in the food chain [3,4]. Thus, scientists focus on finding the proper method for such contamination removal.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations